Molecular detection of blood-borne agents in vampire bats from Brazil, with the first molecular evidence of Neorickettsia sp. in Desmodus rotundus and Diphylla ecaudata - de Mello, Victória Valente Califre [UNESP]; Placa, Ana Julia Vidal [UNESP]; Lee, Daniel Antonio Braga [UNESP]; Franco, Eliz Oliveira [UNESP]; Lima, Luciana; Teixeira, Marta M.G.; Hemsley, Claudia; Titball, Richard W.; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (Elsevier, 2023)
Bats (Mammalia, Chiroptera) represent the second largest group of mammals. Due to their ability to fly and adapt and colonize different niches, bats act as reservoirs of several potentially zoonotic pathogens. In this context, the present work aimed to investigate, using molecular techniques, the occurrence of blood-borne agents (Anaplasmataceae, Coxiella burnetii, hemoplasmas, hemosporidians and piroplasmids) in 198 vampire bats sampled in different regions of Brazil and belonging to the species Desmodus rotundus (n = 159), Diphylla ecaudata (n = 31) and Diaemus youngii (n = 8). All vampire bats liver samples were negative in PCR assays for Ehrlichia spp., Anaplasma spp., piroplasmids, hemosporidians and Coxiella burnetii. However, Neorickettsia sp. was detected in liver samples of 1.51% (3/198) through nested PCR based on the 16S rRNA gene in D. rotundus and D. ecaudata. This is the first study to report Neorickettsia sp. in vampire bats. Hemoplasmas were detected in 6.06% (12/198) of the liver samples using a PCR based on the 16S rRNA gene. The two 16S rRNA sequences obtained from hemoplasmas were closely related to sequences previously identified in vampire and non-hematophagous bats from Belize, Peru and Brazil. The genotypic analysis identified a high diversity of bat-associated hemoplasma genotypes from different regions of the world, emphasizing the need for studies on this subject, in order to better understand the mechanisms of co-evolution between this group of bacteria and their vertebrate hosts. The role of neotropical bat-associated Neorickettsia sp. and bats from Brazil in the biological cycle of such agent warrant further investigation.
Keywords: Anaplasmataceae; Chiroptera; Haemosporidians; Hemoplasmas; Neorickettsia; Piroplasmids